TERMINAL NODE CONTROLLER FOR APRS NETWORK - ROMANENKO, ANTON; KOROTKYI, IEVGEN (Herald of Khmelnytskyi National University. Technical sciences, 2023)
A solution based on APRS technology is proposed for alternative communication between users in "blackout" conditions, in the absence of global communication coverage. The structure and operation principle of APRS technology are described. The process of designing and configuring the controller of the APRS network node is considered, as well as the use of APRS for data transmission between mobile devices. In particular, the frame format of the AX.25 protocol used in APRS, the KISS protocol for data transmission from the client mobile device through the serial interface, and the implementation of the physical layer of APRS, including AFSK modulation/demodulation and scrambling, are discussed. The proposed solution is an APRS network node controller, which is connected to the walkie-talkie radio via an audio headset port. Interaction between the developed APRS network node controller and user mobile devices is carried out via a wireless connection using a Bluetooth serial port. The hardware is based on the affordable ESP32 microcontroller series, which reduces the time of solution implementation due to the availability and low cost of components. The schematic solutions used to connect to the walkie-talkie’s headset are described. The project is implemented based on the open-source ESP32TNC software, which allows modifying the operation algorithm for specific tasks, including adapting the controller for remote system control. A prototype of the proposed solution has been created. Oscillogram and spectrum measurements of the AFKS-modulated signal were performed for the developed prototype. Using the developed solution, maximum communication distance was measured in a densely built-up city, namely in the Dniprovskyi District of Kyiv. During the research, APRSdroid was used as client software, and Baofeng UV-5R was used as the walkie-talkie radio with a declared transmission power of 5 W.